A NEW APPROACH TO THE PROBLEM OF AFGHANISTAN - Karimov Azizbek Avazbekovich (Journal of new century innovations, 2023)
Annotation: The scientific article provides information about the benefits of maintaining a peaceful and stable situation in Afghanistan for the region and everyone's equal responsibility for it.